Shaping views: use and reshaping of landscape by medieval elites as exemplified by the case study of Merkenstein castle (Austria) - Siegmeth, Nora (Medieval Settlement Research, 2025)
Merkenstein Castle is located in the eastern part of Austria, at the outskirts of a forest, overlooking flat plains near the country’s border. An in-depth analysis of a digital terrain model of the surrounding area showed numerous traces of change and adaptation of the land. This includes a deserted medieval village, to which relics of crop fields and vineyards belonged, and an intricate old trail network. In this paper, phases of change of dominion Merkenstein are reconstructed, the choice of location for several respective features is investigated, and the extent of visual connections between the social elite and the public are explored.